2013
DOI: 10.1186/1532-429x-15-81
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear stress measured by phase contrast cardiovascular magnetic resonance in children and adolescents with pulmonary arterial hypertension

Abstract: BackgroundPulmonary arterial hypertension (PAH) is a devastating disease with significant morbidity and mortality. At the macroscopic level, disease progression is observed as a complex interplay between mean pulmonary artery pressure, pulmonary vascular resistance, pulmonary vascular stiffness, arterial size, and flow. Wall shear stress (WSS) is known to mediate or be dependent on a number of these factors. Given that WSS is known to promote architectural vessel remodeling, it is imperative that the changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 36 publications
9
61
1
1
Order By: Relevance
“…15,16 We found the in-plane systolic WSS to be 0. Representative four-dimensional flow cardiac magnetic resonance imaging main pulmonary artery (MPA) flow patterns in a control subject (top) and a subject with pulmonary arterial hypertension (PAH; bottom) at different stages of the cardiac cycle.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…15,16 We found the in-plane systolic WSS to be 0. Representative four-dimensional flow cardiac magnetic resonance imaging main pulmonary artery (MPA) flow patterns in a control subject (top) and a subject with pulmonary arterial hypertension (PAH; bottom) at different stages of the cardiac cycle.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, time-averaged WSS over the cardiac cycle (WSS TA ) was calculated as described elsewhere. 16 …”
Section: Wss Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…20-23 Truong et al recently used 2D phase contrast of the right pulmonary artery to measure WSS in children with pulmonary artery hypertension. 24 However, the impact of BAV on changes in blood flow and the association with age and aortic size is poorly understood. In this pilot study, our aim was to describe the influence of BAV on thoracic aorta hemodynamic parameters in a group of pediatric and young adult patients using 4D flow MRI.…”
mentioning
confidence: 99%
“…Others have looked at wall shear stress in pulmonary arteries by phase contrast imaging in CMR and identified that it is decreased in patients with PAH relative to controls due to greater pulmonary artery dilatation with preserved systolic flow. This abnormal shear stress is believed to affect cellular mechanics, with altered inflammatory cytokine expression in more distal vessels, resulting in the medial hypertrophy and vascular pathology seen in PH [28*]. …”
Section: Introductionmentioning
confidence: 99%